Analisis Sistem Kemitraan Digital pada PT X - Muhamad Yudha Waningpati; Christian Wiradendi Wolor; Eka Dewi Utari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study explores the digital partnership system implemented by PT X in engaging with MSMEs and freelance workers. Using a qualitative case study approach, data were collected through in-depth interviews and participatory observation. The findings reveal that while PT X's platform facilitates economic opportunities, it also creates new forms of dependency and inequality. Algorithmic opacity, unbalanced revenue-sharing schemes, and limited user control challenge the fairness and sustainability of such partnerships. This study suggests that digital platforms must rethink their governance and algorithm design to ensure equitable and inclusive collaboration with partners in Indonesia.